Public Debt and Economic Growth in Emerging Market Economies. (6th March 2015) - Fincke, Bettina; Greiner, Alfred
Abstract This paper empirically studies the relationship between public debt and economic growth for selected emerging market economies by performing panel data estimations. The results reveal a statistically significant positive correlation between public debt and the subsequent growth rate of per capita gross domestic product (GDP). Population and investment are also positively correlated with per capita growth, whereas the initial level of real GDP per capita exerts a negative influence on growth, implying conditional convergence. Other variables such as the inflation rate, the trade balance or the exchange rate do not yield a statistically significant effect with respect to economic growth.